Statistical Simmulation of Definite Integral Based on Uppersum and Lowersum Random Partitions using Geogebra - Widiya Astuti Alam Sur (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
The aim of this paper is to present the statistical model simmulation about the definite integral concept based on upersum and lowersum random partitions by using geogebra. The random partitions of the uppersum and lowersum in determine the value of definite integral is used to find out the statsitical distribution of its generated random variable. Based on Kolmogorov Smirnov Test, the random variable data of subinterval partitions on uppersum and lowersum by using goegebra followed the certain statistical distribution. The random partitions of uppersum and lowersums followed Burr 4 parameter, Log-Pearson 3, and Pearson 6 distributions.